Model Development of NIÑO 3.4 and Indian Ocean Dipole (IOD) Anomalies Teleconnection - Saputra, Antonni; Hermawan, Eddy; Darmawan, Denny (Jurnal Sains Dasar, 2018)
The purpose of this research is to develop the teleconnection model of Niño 3.4 and IOD anomalies which can be used as reference to explain precipitation anomalies. El-Niño and IOD cycles are shown as the warming process of sea surface temperatures where for El-Niño is in the Pacific Ocean and IOD is in the Indian Ocean and each of them forms a cycle over a certain period of time. The method used to determine the dominant oscillation of the teleconnection of Niño 3.4 and IOD anomalies is Power Spectral Density (PSD), and to model the teleconnection of Niño 3.4 and IOD anomalies is ARIMA (Autoregressive Integrated Moving Average). The data used are Niño 3.4 index which is one type of index for El-Niño and IOD index. The results are Power Spectral Density (PSD) graphs for the teleconnection of Niño 3.4 and IOD anomalies which oscillates around 5 years. By the ARIMA method, the approximate model for the data of teleconnection of Niño 3.4 and IOD is ARIMA (1,1,2) with equation of Zt = 1.516  Zt-1 - 0.516 Zt-2 - 0.256 at-1 + 0.021 at-2.